Recent advances in molecular techniques for the identification of phytopathogenic fungi – a mini review - Sidra Aslam; Aisha Tahir; Muhammad Farhan Aslam; Muhammad Waqar Alam; Arshad Ali Shedayi; Sehrish Sadia (Journal of Plant Interactions, 2017)
At present, 1.5 million species of fungi are estimated. Among these less than 5% have been described. Many fungal species cause disease in plants. These diseases cause major economic and production losses in the agricultural industry worldwide. Monitoring plant health and detecting the pathogen early are essential to reduce the disease spread, and facilitate effective management practices. DNA-based methods now provide essential tools for accurate plant disease diagnosis. Recently, effective amplification platforms, probe development, various quantitative PCR, DNA barcoding and RNA-Seq-based next-generation sequencing have revolutionized the research in fungal detection field, and differentiation area. Although the molecular diagnostics techniques have grown extensively over the last couple of decades but still there is a long way to go in the development and application of molecular diagnostics to assist the plant disease diagnosticians. Finally, molecular diagnostic techniques used in plant disease diagnostic clinics need to be robust, reliable, inexpensive and easy to be used that they can compete with, and complement traditional techniques. Challenge now remains residue with the researchers to develop the practical techniques used for diagnostic setting. Examples of the recent advancement in the molecular techniques for diagnosing the fungi causing plant disease are discussed in the review. Abbreviations: PCR: polymerase chain reaction; LAMP: loop-mediated isothermal amplification; RCA: rolling circle amplification; NASBA: nucleic acid sequence-based amplification; ITS: internal transcribed spacer; RT: reverse transcriptase; FEB: Fusarium ear blight; qPCR: real-time PCR; SNPs: single nucleotide polymorphism; HRCA: hyper-branched RCA; FIP: forward inner primer; BIP: backward inner primer; COX I: cytochrome c oxidase I; MBs: molecular beacons.